Etnobotani Pengobatan Tradisional Suku Melayu Desa Bagan Punak Pesisir, Rokan Hilir, Provinsi Riau - Sri Wahyuni; Afidah, Mar’atul; Awal, Raudhah; Sari, Ermina (Universitas Lancang Kuning, 2025)
This research aims to determine the types of plants used, the parts used, how traditional medicine is used and the meaning countained contained in the traditional medicine of the Malay tribe in the Bagan Punak Pesisir Village by documenting ethnobotanical knowledge in traditional medicine in Bagan Punak Pesisir Village, Bangko District, Rokan Hilir Regency, Riau province. The research method used is a survey method with interview and observation techniques. The data collected includes the type of medicinal plant used, the part of the plant used and its medicinal benefits. The results of the research show that there are 7 types of medicinal plants used by the Malay community in Bagan Punak Pesisir Village. These medicinal plants come from various plant families, with the Zingiberaceae, Piperaceae, Acoraceae, Arecaceae and Rubiaceae tribes. The most commonly used plant parts are rhizomes (57.14%), followed by leaves (14.28%), sap (14.28%), and fruit (14.28%). Diseases treated with medicinal plants are fever, headaches and restoring enthusiasm. Ethnobotanical knowledge in traditional Malay medicine in Bagan Punak Pesisir Village is a cultural heritage that needs to be preserved.